MULTIMEDIA JOURNALISM: TOOLS AND EXPERIENCE OF USING IN THE KAZAKHSTANI MASS MEDIA (Herald of Journalism, 2018)
The article describes theoretical foundations of multimedia journalism and shows examples of thepractical usage of the modern technologies in the Kazakhstani Internet Mass media. The author delineatesthe concepts «Multimedia journalism» and «Convergence journalism». On the base of an analysis ofpublications of the Kazakhstani news media, actively using new informational technologies, the authorillustrates the basic multimedia genres and draws conclusions about the experimental and non-uniformcharacter of the development of multimedia journalism in Kazakhstan.